2018
DOI: 10.17743/jaes.2018.0001
|View full text |Cite
|
Sign up to set email alerts
|

Elicitation of Expert Knowledge to Inform Object-Based Audio Rendering to Different Systems

Abstract: Object-based audio presents the opportunity to optimize audio reproduction for different listening scenarios. Vector base amplitude panning (VBAP) is typically used to render objectbased scenes. Optimizing this process based on knowledge of the perception and practices of experts could result in significant improvements to the end user's listening experience. An experiment was conducted to investigate how content creators perceive changes in the perceptual attributes of the same content rendered to systems wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Literature pertaining to envelopment was used to suggest parameters that met the second criterion. An experiment performed by Woodcock et al [35] investigated the parameters that mixing engineers would use to make manual changes to object-based audio that had been rendered to different loudspeaker layouts, as well as selecting the perceptual attributes that had changed as a result of the rendering. The responses were clustered into a set of parameters (spread, EQ and processing, reverb, position, bass, and level) that were all found to show a significant relationship to changing envelopment.…”
Section: Parametersmentioning
confidence: 99%
“…Literature pertaining to envelopment was used to suggest parameters that met the second criterion. An experiment performed by Woodcock et al [35] investigated the parameters that mixing engineers would use to make manual changes to object-based audio that had been rendered to different loudspeaker layouts, as well as selecting the perceptual attributes that had changed as a result of the rendering. The responses were clustered into a set of parameters (spread, EQ and processing, reverb, position, bass, and level) that were all found to show a significant relationship to changing envelopment.…”
Section: Parametersmentioning
confidence: 99%
“…Downmixing based on metadata adaptation is particularly useful for systems where VBAP rendering is not possible without introducing virtual loudspeakers into the configuration, such as two-channel stereo. A benefit to this approach over traditional matrix downmixing methods is that it allows downmixing rules to be specified for different categories of audio objects-it has recently been shown that mix engineers apply different processes to different categories of audio objects when downmixing object-based audio to different systems [10].…”
Section: Intelligent Downmixingmentioning
confidence: 99%
“…Metadata transformations may be derived from psychoacoustics, subjective listening experiments, or expert knowledge. For example, rules for automatic repositioning of sound objects were derived from re-mixing experiments with sound engineers [10] (see Sec. 2.1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Treating the variPlay stems as objects and embedding appropriate metadata would have provided numerous creative mix/mastering opportunities, but this would also have incurred considerable DSP at the point of rendering and so was avoided. This is the approach proposed by Woodcock et al (2018) specifically for content creators to replicate mix characteristics at the point of rendering. Furthermore, it was not possible to implement passive app-native processing on the output buss due to such CPU-loading considerations, especially for compatibility with older phones.…”
Section: Mastering For Variplaymentioning
confidence: 99%